2018
DOI: 10.18203/2349-2902.isj20180362
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictors of a difficult laparoscopic cholecystectomy

Abstract: Background: Laparoscopic cholecystectomy (LC), the gold standard of treatment of gallstone disease, is a widely performed surgery, but it can become a challenge to complete at times. Aim of present study was to find out the possible preoperative features in a gallstone disease patient that predispose him to having a difficult LC. Methods: All cases of gallstone disease undergoing LC at a tertiary care hospital were studied over one year. Patients with jaundice, abnormal liver function tests, concomitant common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
2
6
1
1
Order By: Relevance
“…11 Vivek et al described similar results when they reported the role of increasing age, male gender, high BMI, previous biliary disease, previous surgery, and preoperative sonological findings in accurately predicting the intra operative difficulties of laparoscopic cholecystectomy. 12 Similar results were also obtained by Gupta et al and Kulkarni et al 13,14 The study found the scoring system developed by Randhawa and Pujari et al to have a sensitivity of 77.8%, specificity of 78.1%, positive predictive value of 66.7% and a negative predictive value of 86.2% in the prediction of difficult laparoscopic cholecystectomies. However, Randhawa and Pujari et al reported a sensitivity and specificity of 75.00% and 90.24%, respectively.…”
Section: Discussionsupporting
confidence: 64%
“…11 Vivek et al described similar results when they reported the role of increasing age, male gender, high BMI, previous biliary disease, previous surgery, and preoperative sonological findings in accurately predicting the intra operative difficulties of laparoscopic cholecystectomy. 12 Similar results were also obtained by Gupta et al and Kulkarni et al 13,14 The study found the scoring system developed by Randhawa and Pujari et al to have a sensitivity of 77.8%, specificity of 78.1%, positive predictive value of 66.7% and a negative predictive value of 86.2% in the prediction of difficult laparoscopic cholecystectomies. However, Randhawa and Pujari et al reported a sensitivity and specificity of 75.00% and 90.24%, respectively.…”
Section: Discussionsupporting
confidence: 64%
“…In our study, neither the number of acute attacks, nor the conversion found to be significantly associated with increasing GBWT this is contrast to what Nidoni et al [6] found in their study where they reported statistically significant association between the rate of conversion to open and number of acute attacks. Majority of our patients who had multiple stones which were not impacted, had a normal GBWT; in contrast to Kulkarni and Kumar who stated that; multiple stones increased surgeon's difficulty and impacted stone in gallbladder neck increased the conversion rate [20].…”
Section: Resultscontrasting
confidence: 58%
“…Majority of patients had multiple stones which were not impacted, had normal gallbladder caliber and normal wall thickness; in contrast to Kulkarni and Kumar et al who stated that multiple stones increased surgeon's difficulty and impacted stone in gallbladder neck increased the conversion rate [7].…”
Section: Resultsmentioning
confidence: 87%
“…Randhawa and Pujahari[ 3 ] came up with a systemic scoring system to predict the level of difficulty in LC. This scoring system takes into account demographic factors such as age,[ 4 - 7 ] gender,[ 8 ] hospitalization history for acute cholecystitis,[ 9 , 10 ] clinical factors such as BMI,[ 11 ] the presence of abdominal scar,[ 12 ] palpability of gallbladder, and sonographic features such as wall thickness,[ 13 ] pericholecystic collection, and impacted stone[ 14 , 15 ] as the predictors of difficulty.…”
Section: Discussionmentioning
confidence: 99%